Soil Moisture Sensor for Precision Agriculture - Singh, Sneha (Journal of Advanced Research in Instrumentation and Control Engineering; Vol 7 No 2 (2020): Journal of Advanced Research in Instrumentation and Control Engineering (ISSN 2456-1398), 2020)
Irrigation and farming has been the core of our economy.  Soil   moisture   has   great   significance   as   it is important for plants growth. Here, The significant contribution in the changing the way in which irrigation has been employed and executed over  the  years. This work presents an implementation of a customized system which monitors the moisture level of the soil and waters the plants as per the requirements Water plays a vital role in irrigation. Efficient irrigation watering not only saves water, but provides better plant yields, reduces dependency on fertilizers and recovers crop quality. As there is an increase of demand for food, measuring soil moisture will get more and more significant. There are variety of methods used to measure soil moisture content, but the best one is utilizing the soil moisture sensor devices. For efficacious irrigation, it is necessary to check soil moisture content continuously in the irrigation fields. The soil moisture probes selection is one of the most significant criteria in calculating soil moisture. The soil moisture sensors usage is high nowadays as it gives real time readings. How to cite this article Singh S, Shukla S. Soil Moisture Sensor for Precision Agriculture. J Adv Res Instru Control Engg 2020; 7(2): 4-7.